(untitled) (Tokyo, 1976)
This book introduce a history of Japanese geography. General comments on the development of physiscal geography in Japan. General remarks on human geography during the past fifty years...
Keywords: Địa lý,Geography; Giảng dạy và học tập,Study and teaching; Nhật Bản,Japan